The possible cause of most intense geomagnetic superstorm of the 21st century on 20 November 2003 - Raghav, Anil; Shaikh, Zubair; Vemareddy, P.; Bhaskar, Ankush; Dhamane, Omkar; Ghag, Kalpesh; Tari, Prathmesh; Dayanandan, Baiju; Suti, Badar Mohammed Al (My University, 2023)
An extreme geomagnetic storm has the potential to affect various technologies and activities in space and on the ground, e.g., power grids, oil and gas industries, communications, ground transportation, satellite infrastructure, global navigation satellite systems, aviation, etc. Therefore, it is considered a major source of risk by various governmental agencies and corporations at the international level. All notable space weather events (superstorms) are caused by interplanetary coronal mass ejections (ICMEs). But not every ICME leads to an extreme storm. Moreover, how does an extreme storm form? Or which explicit characteristic of ICME actually is responsible for inducing a superstorm? Here, we re-investigate the ICME characteristics that contribute to the most intense storm of the current century that occurred on 20 November 2003. Interestingly, the studied ICME magnetic cloud shows characteristics of extremely flattened (pancaked) structure i.e. quasi-planar magnetic structure (PMS). The pancaked ICME shows less adiabatic expansion than usual in the compressed direction, which leads to strong magnetic field strength, high plasma density, high solar wind speed, high dynamic pressure, and a high eastward interplanetary electric field. Here, we propose that the ICME that transformed into a quasi-PMS has the aforementioned enhanced features with strong southward magnetic field component that contributes to efficiently transferring plasma and energy into the Earth’s magnetosphere to cause the observed superstorm.
Keywords: The Sun: coronal mass ejections (CMEs); Coronal mass ejections (CMEs); Solar-terrestrial relations; Heliosphere; Solar wind